He’s Variational Iteration Method for Nonlinear Jerk Equations: Simple but Effective - Behrouz Raftari (Shock and Vibration)
The variational iteration method (VIM) for determining periodic solutions of non-linear jerk equations involving third-order time-derivative is presented. This method is based on the use of Lagrange multipliers for identification of optimal value of a parameter in a functional. We propose first-order approximate VIM solution for this equation and we compare this solution with the solution obtained by harmonic balance method.